Changing patterns in the workload of a district HIV/AIDS counselling unit 1987-90. Issue 3 (June 1991) - Bor, R; Elford, J; Campbell, L; Salt, H; Miller, R; Murray, D; Johnson, M
Abstract : OBJECTIVES–To describe the changing workload of an HIV/AIDS counselling unit between 1987 and 1990. DESIGN–Retrospective examination of data collected by the HIV/AIDS counselling unit between 1987-90 on the number of counselling sessions with patients, family members and staff. SETTING–An HIV/AIDS counselling unit established in 1987 in a London teaching hospital. MAIN OUTCOME MEASURES–Number of new referrals to the HIV/AIDS counselling unit and the number of follow-up sessions. Number of counselling sessions with family members, hospital staff and people making telephone contact with the unit. RESULTS–New referrals to the HIV/AIDS counselling unit increased from 117 (1987-88) to 926 (1989-90). Follow-up appointments increased from 403 to 2016 in the same period. Telephone counselling sessions increased five-fold, and counselling sessions with family members nearly ten-fold over the three year period. Staff consultations doubled. CONCLUSION–The increase in the HIV/AIDS counselling unit's workload may be partly attributable to the rising incidence of AIDS in the community, reflecting earlier patterns of HIV infection. In addition, new HIV/AIDS services were developed in the hospital between 1987 and 1990. These included the establishment of a same-day HIV test and result clinic; integrated management of patients with HIV/AIDS, with an emphasis on early intervention in HIV infection; specialist services for families, antenatal clinic attenders and others affected by HIV; and the appointment of a designated HIV/AIDS consultant. New approaches to counselling and training health care providers in counselling skills will assume increasing importance in meeting future demand for HIV/AIDS counselling.